Penerapan Metode Muhadatsah untuk Meningkatkan Kemampuan Berbahasa Arab Siswa di MTs Daarul Muhajirin Kota Bogor - Alfiyah Fathekhahsari; Santi Lisnawati; Retno Triwoelandari (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
The purpose of this study was to determine the use of Muhadatsah method in improving students ' Arabic language skills in learning Arabic at Madrasah Tsanawiyah (MTs) Daarul Muhajirin Bogor City. This type of research is a class action research (PTK) designed in two cycles. Instruments used in this study are observation sheets of teacher and student activities, and test sheets. Data collection techniques using observations and tests. Data analysis techniques using qualitative descriptive analysis and quantitative descriptive analysis. The results showed that there was an increase in Arabic language proficiency of students from pre-cycle, cycle I to Cycle II, which can be seen from the results of the Learning test that is from 25 students in the pre-cycle completed only 9 students with a percentage of 36% and has not met the classical completeness, in cycle I as many as 13 students with a percentage of 52%, and in Cycle II as many as 23 students with a percentage of 92%, this shows an increase from pre-cycle to cycle I and Cycle II and has met the classical completeness. So it can be concluded that the use of Muhadatsah method can improve the Arabic language skills of students at Madrasah Tsanawiyah (MTs) Daarul Muhajirin Bogor City.